2018
DOI: 10.1103/physrevb.98.024522
|View full text |Cite
|
Sign up to set email alerts
|

Short-time dynamics in s+is -wave superconductor with incipient bands

Abstract: Motivated by the recent observation of the time-reversal symmetry broken state in K-doped BaFe2As2 superconducting alloys, we theoretically study the collective modes and the short time dynamics of the superconducting state with s + is-wave order parameter using an effective four-band model with two hole and two electron pockets. The superconducting s + is state emerges for incipient electron bands as a result of hole doping and appears as an intermediate state between s ± (high number of holes) and s ++ (low … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Indeed, a recent numerical study of Terahertz induced gap dynamics for s + is pairing has revealed an unusual coupling between the Higgs amplitude and the Leggett (relative) phase mode. 50 Exact solutions of the time-dependent two-band BCS model only exist for special fine tuned values of the intraand inter-band interaction parameters, where the problem effectively reduces to the single-band case (see below and Ref. 49).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent numerical study of Terahertz induced gap dynamics for s + is pairing has revealed an unusual coupling between the Higgs amplitude and the Leggett (relative) phase mode. 50 Exact solutions of the time-dependent two-band BCS model only exist for special fine tuned values of the intraand inter-band interaction parameters, where the problem effectively reduces to the single-band case (see below and Ref. 49).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the subdominant d x 2 −y 2 symmetry within the OSSF model is beyond the scope of this work. However, we expect that the inclusion of the orbital degree of freedom within multiband approaches implemented so far (see, e.g., [36][37][38][39][40]) could provide further insight on the SC properties of IBS.…”
Section: Discussionmentioning
confidence: 99%
“…Such states can host multiple interesting phenomena, such as massless modes 5,14 , mixed collective modes 5,[15][16][17][18][19][20][21][22] , new flux flow phenomena 23 , stable and metastable Skyrmions [24][25][26] , new thermoelectric effects 27,28 and new fluctuation-induced phases 3,[29][30][31] .…”
Section: Introductionmentioning
confidence: 99%